'And we are a human being': Coproduced reflections on person‐centred psychotherapy in plural and dissociative identity. (16th February 2021) - Blunden, Nicola; Billie,
Abstract: In this reflexive case‐study, 'Billie', an integrative psychotherapist, and her therapist, Nicola, offer a coproduced account of Billie's lived experience of dissociative identity. Challenging the medicalised 'fragmentation towards integration' discourse, Billie, her parts, and Nicola coproduce a person‐centred 'exclusion towards inclusion' approach. The authors propose the term 'plural identity', situating the experience less as a disorder, and more as a way of being human. They present verbatim extracts of their therapeutic work, with parallel commentary and postsession discussion, to illustrate their developing, person‐centred and coproduced approach towards intrapsychic inclusion. They conclude that inclusion consists in unconditionally valuing three prevailing constituents in plural identity: the individual parts of self; the ecological system; and the differentiation between parts. This can result in growth for all parts, including parts that initially appear counter to growth, and allows the lived experience of the client to be honoured, not pathologised.